Molecular cloning and characterization of Rheb from white shrimp (Litopenaeus vannamei) - X Liu (Invertebrate Survival Journal, 2018)
The Ras family GTPase Rheb, a GTP-binding protein, binds specifically to the mTOR catalytic domain and induces activation of the mTOR catalytic function. Furthermore, Rheb is related to a stable modification of the configuration of mTORC1 that increases access of substrates to their binding site on the raptor polypeptide. In the present research, a cDNA of 898 bp for the Litopenaeus vannamei Rheb was cloned via rapid amplification of cDNA ends (RACE) technique. The complete cDNA sequence of Rheb contained an open reading frame (ORF) of 549 bp, which encoded a protein of 182 amino acids. The amino acid sequence of Rheb shared more than 60% similarity with other identified Rheb proteins. A Ras domain (from P3 to A169) was found in the amino acid sequence of Rheb that can react selectively and non-covalently with GTP. The mRNA transcripts of Rheb were consistently expressed in all the tested tissues, including muscle, gill, hepatopancreas, eyestalk, intestine and stomach. The mRNA expression profiles of Rheb in muscle after the stimulation with rapamycin were promoted, which further proved that Rheb protein could be a feedback regulator to mTOR signaling pathway. Furthermore, the results of the present study indicated that Rheb played an important role in the regulation of mTOR signaling pathway during the stimulation of dietary restriction, amino acid supplementation and rapamycin stimulation in shrimp.